"THE MASKING GOD": Engaging Roger Haight and Wilfred Cantwell Smith in Search of the Living God in the Ongoing Deadly Covid-19 Pandemic - Parulihan Sipayung (MAHABBAH: Journal of Religion and Education, 2022)
This study phenomenologically aims to reconsider the understandings and practices of religions in ongoing deadly Covid-19 pandemics. Religions and their naivety have become the pandemic within pandemic. Religions pretend to behave like God and the followers obey them uncritically and sometimes irrationally. This study argues that religions should become a window that through it the followers can experience the liberating presence of God who is characteristically pro-life and love. I argue whatever concept of truth religions have, life, and love must be the character of true faith in a true God. This study limitedly investigates global religious phenomena during the covid-19 pandemic all over the world and endeavors to give a theological appraisal based on the theology of Roger Haight and Wilfred Cantwell Smith. In conclusion, I argue, God is indeed present in human life but not transparently. God reveals God-self with a theo-philosophical mask. Thus, God is a masking God.  Therefore, to understand God we should debunk the naïve understanding of religion and go beyond the religious phenomena to the absolute mysterious reality of God–The ‘Wholy Mysterious Other’.